UPAYA KEWIRAUSAHAAN DALAM MENINGKATKAN KEMANDIRIAN EKONOMI LEMBAGA PENDIDIKAN ISLAM - HJ. ZULHIMMA S.Ag., M.Pd (Institut Agama Islam Negeri Padangsidimpuan, 2018)
Management of Islamic education institutions must be able to play an active role in preparing human resources who are able to face the challenges of life today. The knowledge obtained in educational institutions should be practiced in daily life, not just mastery of theory. In the implementation of Islamic education mastery of life skills is an important thing obtained by students through entrepreneurship education. Entrepreneurship education is an effort to foster a mental and mental attitude that is always active or creative in power, creation, initiative and modesty in trying to increase income in business activities. In fulfilling the educational needs to realize quality schools, there is a need for a large amount of funding. It requires the leadership's creativity to look for opportunities that can be utilized for the progress of the institution and also strive towards economic independence